Examination of Applicability of Engine Condition Trend Monitoring to Bell 2068 Ill Helicopter - Mistrić, Davor; Eleršek, Leonard; Bazijanac, Ernest (Promet - Traffic&Transportation, 2002)
Because of the advantages of turboshaft engine conditiontrend monitoring, it is in the interest of the Croatian Air Forceto examine its applicability in Bell 206B Ill helicopter maintenancesystem.The paper deals with the basic of turboshaft engine conditiontrend monitoring procedure; and describes also the procedurefor Allison 250 C20J engine, which is installed in Bell206B Ill. Results of parameter readings are presented and reasonsof inapplicability of condition trend monitoring within pilottraining process are explained. Alternative procedure is recommended.